Multifaceted empathy of healthy volunteers after single doses of MDMA: A pooled sample of placebo-controlled studies. (May 2017) - Kuypers, Kim PC; Dolder, Patrick C; Ramaekers, Johannes G; Liechti, Matthias E
Previous placebo-controlled experimental studies have shown that a single dose of MDMA can increase emotional empathy in the multifaceted empathy test (MET) without affecting cognitive empathy. Although sufficiently powered to detect main effects of MDMA, these studies were generally underpowered to also validly assess contributions of additional parameters, such as sex, drug use history, trait empathy and MDMA or oxytocin plasma concentrations. The present study examined the robustness of the MDMA effect on empathy and investigated the moderating role of these additional parameters. Participants ( n = 118) from six placebo-controlled within-subject studies and two laboratories were included in the present pooled analysis. Empathy (MET), MDMA and oxytocin plasma concentrations were assessed after oral administration of MDMA (single dose, 75 or 125 mg). Trait empathy was assessed using the interpersonal reactivity index. We confirmed that MDMA increased emotional empathy at both doses without affecting cognitive empathy. This MDMA-related increase in empathy was most pronounced during presentation of positive emotions as compared with negative emotions. MDMA-induced empathy enhancement was positively related to MDMA blood concentrations measured before the test, but independent of sex, drug use history and trait empathy. Oxytocin concentrations increased after MDMA administration but were not associated with behavioral effects. The MDMA effects on emotional empathy were stable across laboratories and doses. Sex did not play a moderating role in this effect, and oxytocin levels, trait empathy and drug use history were also unrelated. Acute drug exposure was of significant relevance in the MDMA-induced emotional empathy elevation.